BROKEN HOME BAGI ANAK PASCAPERCERAIAN KEDUA ORANG TUA DI PENGADILAN AGAMA PERSPEKTIF MAQOSID SYARI’AH - Syeh Sarip Hadaiyatullah (Jurnal GeoCivic, 2025)
Divorce among parents often leads to the failure of a marriage to achieve its primary goals, which are sakinah, mawaddah, warahmah (peace, love, and compassion). In family law courts, the number of divorces continues to rise every year, reflecting a growing trend of broken marriages. This situation undermines the intended harmony and stability that marriage is supposed to bring, leaving a significant impact on the family unit as a whole. This study aims to determine the psychological impact on children after their parents' divorce. This study uses a descriptive qualitative method. The qualitative approach taken is a qualitative case study approach. Parental divorce can have a significant psychological impact on children. Children may experience stress, anxiety, and feelings of insecurity. They can also feel guilty, lose self-confidence, and have difficulty building healthy relationships in the future. Some children even exhibit aggressive, quiet, or withdrawn behavior in response to their parents' divorce.